INTERFAITH MARRIAGE THE VIWES OF ISLAMIC SCHOLARS AND NATIONAL LAW - Achmad Hasan Alfarisi; Moh Rokib (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2024)
The prohibition and the views of scholars interfaith marriage in Indonesia is further strengthened by the Constitutional Court Decision Number 24/PUU-XX/2022 and the issuance of the Supreme Court Circular Letter Number 2 of 2023 which has very broad implications. Not only does it affect marriage practices, but it also has a significant impact on the marriage registration system. Interfaith marriage in Indonesia also presents a number of complex legal problems for children born from such marriages. Children in these marriages often do not receive adequate legal protection because of the marriage so that they only have a civil relationship with their mother. In the legal context, children often face uncertainty regarding their legal status and legitimacy, because interfaith marriages in Indonesia are not recognized by the state. In terms of custody, if a divorce occurs, several problems arise, including to whom custody will be given. Regarding this problem, policy reform is expected because there is an urgent need for legal regulations to protect the rights of children born from interfaith marriages and provide legal justice for these children.